Avaliação da sensibilidade do índice de rapidez muscular e de testes funcionais para identificação de idosas com histórico de quedas - Corrêa , Talyene Gleice Costa (2019)
Background: Aging is a natural process characterized by a progressive decline in sensory, motor and cognitive abilities. Such a decline increases the risk of falls in elderly individual s. Outcome variables that are sensitive to indicate the risk of falls in the elderly are still needed . The rate of force development scaling factor (RFD SF) obtained in tests involving force production at submaximal levels could be a candidate to be a bio m arker for fall risk . Aim: To examine the sensitivity of outcome variables obtained in different tests to discriminate elderly women with and without a history of falls and to determine which outcome would be the most sensitive. M ethods Forty eight, betwee n 62 and 85 years of age performed the timed up and go test (TUG T ), the five times sit to stand test (5xSTST) and two tests that used an instrumented handle to measure the digital grip strength. In the first test the participants reach ed the maximum force (first 3 trials) and maximum force as fast as possible. Maximum digital grip strength and maximum rate of digital grip force development were calculated. In the second, they performed sequencies of force pulses performed as fast as possible and in differe nt percentages of maximum strength to obtain the rate of force development scaling factor . Results: According to the history of falls, 25 fallers (one or more falls in the last 12 months) and 23 were non fallers (no history of falls) were identified. There was no statistically significant difference between the groups of fallers and non fallers for all the variables analyzed, except for the TUG T , in which the fallers took longer to perform the test when compared to non fallers . Conclusion : Outcomes from t es ts involving digits force production were not sensitive to differentiate elderly women with a history of falls from those with no history of falls. The TUG T was the only test that could distinguish elderly women with and without a history of falls.